Legal Awareness of Design Rights Registration For The Sasak Woven Fabric Industry - Abdullah, Junaidi; Nubahai, Labib; Yaekaji, Aisyah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 2 (2025), 2025)
Sukarara Village in Central Lombok is known for its rich cultural heritage, particularly its unique and highly valued Sasak woven fabric motifs. However, this cultural potential has not been fully protected by law, especially in relation to industrial design rights. This study aims to analyze the legal protection of the moral and economic rights of the creators of Sasak woven fabric designs and to identify the factors influencing the legal awareness of design owners regarding the registration of industrial design rights. This research uses a qualitative method with a field research approach, collecting data directly from the local community and stakeholders in Sukarara Village. The findings indicate that legal protection of moral rights is crucial for preserving the recognition of the creator’s identity and the integrity of the design, while economic rights enable artisans to gain financial benefits from their designs. However, the legal awareness of the community regarding the importance of registering industrial design rights remains low. This is due to a lack of outreach, limited legal understanding, perceptions that the registration process is complicated and expensive, and a tendency to rely more on customary mechanisms. Factors influencing legal awareness include the level of legal knowledge, local legal culture, and economic incentives. Therefore, collaborative efforts are needed through culturally-based education, involvement of traditional leaders, simplification of legal procedures, and cost subsidies to encourage legal protection of Sasak woven designs and improve the welfare of the community. esa Sukarara di Lombok Tengah dikenal dengan kekayaan budaya berupa kain tenun motif khas Sasak yang unik dan bernilai tinggi. Namun, potensi budaya ini belum sepenuhnya terlindungi secara hukum, terutama terkait hak atas desain industri. Penelitian ini bertujuan untuk menganalisis perlindungan hukum terhadap hak moral dan hak ekonomi pencipta desain kain tenun Sasak, serta mengidentifikasi faktor-faktor yang memengaruhi kesadaran hukum pemilik desain terhadap pendaftaran hak desain industri. Penelitian ini menggunakan metode kualitatif dengan pendekatan lapangan (field research) melalui pengumpulan data langsung dari masyarakat dan pemangku kepentingan di Desa Sukarara. Hasil penelitian menunjukkan bahwa perlindungan hukum atas hak moral penting untuk menjaga pengakuan terhadap identitas pencipta dan integritas desain, sementara hak ekonomi memungkinkan pengrajin memperoleh manfaat finansial dari desain tersebut. Namun, kesadaran hukum masyarakat terhadap pentingnya pendaftaran hak desain industri masih rendah. Hal ini disebabkan oleh kurangnya sosialisasi, pemahaman hukum yang minim, persepsi bahwa proses pendaftaran rumit dan mahal, serta kecenderungan masyarakat untuk lebih mengandalkan mekanisme adat. Faktor-faktor yang memengaruhi kesadaran hukum antara lain tingkat pemahaman hukum, budaya hukum lokal, dan insentif ekonomi. Oleh karena itu, diperlukan upaya kolaboratif melalui edukasi berbasis budaya, pelibatan tokoh adat, penyederhanaan prosedur hukum, dan subsidi biaya untuk mendorong perlindungan hukum terhadap desain tenun Sasak dan meningkatkan kesejahteraan masyarakat.